COMPARATIVE CHARACTERISTICS OF PUCCINIA RECONDITA ROB. EX DESM. SYN.: PUCCINIA TRITICI ERIKSS. VIRULENCE IN MIDDLE VOLGA REGION - L. G. Tyryshkin; V. G. Zakharov; V. V. Syukov (Вавиловский журнал генетики и селекции, 2015)
According to a study conducted in 2011–2012, Puccinia recondita populations from Ulyanovsk and Bezenchuk share one geographic range of leaf rust variety formation and dispersal. At the same time, a significant similarity between the structures of the Middle Volga population and of populations from North Caucasus and Northwestern Russia was shown. Clones virulent to Lr 9 and 41 were absent from all regions examined. The virulence genes plr19, plr24, plr28, plr29, plr47 occurred at low frequencies.